Somatic symptom severity association with healthcare utilization and costs in surgical inpatients with an episode of abdominal pain. Issue 4 (7th July 2022) - Stieler, Melissa; Pockney, Peter; Campbell, Cassidy; Thirugnanasundralingam, Vaisnavi; Gan, Lachlan; Spittal, Matthew J; Carter, Gregory
Abstract: Background: Somatic syndromes are present in 30 per cent of primary healthcare populations and are associated with increased health service use and health costs. Less is known about secondary care surgical inpatient populations. Methods: This was a prospective longitudinal cohort study ( n  = 465) of consecutive adult admissions with an episode of non-traumatic abdominal pain, to the Acute General Surgical Unit at a tertiary hospital in New South Wales, Australia. Somatic symptom severity (SSS) was dichotomized using the Patient Health Questionnaire (PHQ)-15 with a cut-off point of 10 or higher (medium–high SSS) and compared pre-admission and during admission. Total healthcare utilization and direct costs were stratified by a PHQ-15 score of 10 or higher. Linear regression was used to examine differences in costs, and a multivariable linear regression was used to examine the relationship of PHQ-15 scores of 10 or higher to total costs, reported as mean total costs of care and percentage difference (95 per cent confidence intervals). Results: Fifty-two per cent ( n  = 242) of participants had a medium–high SSS with greater pre-admission and admission interval health service costs. Mean total direct costs of care were 25 per cent (95 per cent c.i. 8 to 44 per cent) higher in the PHQ-15 score of 10 or higher group: mean difference €1401.93 (95 per cent c.i. €512.19 to €2273.67). The multivariable model showed a significant association of PHQ-15 scores of 10 or higher (2.1 per cent; 0.2–4.1 per cent greater for each one-point increase in score) with total hospital costs, although the strongest contributions to cost were older age, operative management, and lower socioeconomic level. There was a linear relationship between PHQ scores and total healthcare costs. Conclusions: Medium to high levels of somatic symptoms are common in surgical inpatients with abdominal pain and are independently associated with greater healthcare utilization. Abstract : Somatic syndromes are common psychiatric presentations in primary and secondary care, characterized by illness anxiety surrounding physical symptoms. In an inpatient surgical population presenting with abdominal pain, somatic symptom severity was associated with higher inpatient and outpatient healthcare expenditure, and increased duration of hospital stay.